Variation in Essential Oil Content and Chemical Composition of Rosemary (Rosmarinus officinalis L.) at Various Growth Stages in the Mediterranean Region - Muzaffer Barut; Asiye Sena Cavdar; Leyla Sezen Tansı; Sengul Karaman (Turkish Journal of Agriculture: Food Science and Technology)
Rosemary is an aromatic shrub native to the coasts of the Mediterranean region. Understanding the changes of chemical composition of essential oil is critical for more targeted rosemary harvesting, which can lead to higher-quality essential oils for agro-food, medicinal, and cosmetics uses. Therefore, rosemary plants were harvested at pre-flowering, full-flowering, and post-flowering stage grown in the experimental area of the Department of Field Crops at Çukurova University in order to determine the most suitable harvest time for the highest amount of essential oils and their important compounds. Essential oil content decreased slightly from the pre-flowering to post-flowering. The highest essential oil content (1.68%) was determined at the pre-flowering stage. Twenty-eight compounds were found representing 95.74%-96.74% of the total essential oil. The major compounds for rosemary were camphor (28.43%-32.74%), 1,8-cineol (20.80%-22.61%), isoborneol (6.05%-7.28%), verbenol (5.17%-6.98%), and limonene (5.71%-6.23%), respectively. Consequently, the optimal harvest time in terms of essential oil content, as well as camphor, 1,8-cineole and limonene content, may be considered as pre-flowering stage.